Outcomes of posterior wall isolation with pulmonary vein isolation for paroxysmal atrial fibrillation. (3rd January 2022) - Jankelson, Lior; Garber, Leonid; Shulman, Eric; Cohen, Roi Bar; Peterson, Connor; Wadhwani, Lalit; Nadeau‐Routhier, Charles; Xia, Yuhe; Barbhaiya, Chirag; Holmes, Douglas; Knotts, Robert; Bernstein, Scott; et al.
Abstract: Introduction: Prior studies have shown that addition of posterior wall isolation (PWI) may reduce atrial fibrillation recurrence in patients with persistent atrial fibrillation. No data on PWI in paroxysmal AF (pAF) patients with normal left atrial voltage is available, to date. Objective: This study sought to evaluate the efficacy of PWI in addition to pulmonary vein isolation (PVI) in patients presenting with pAF and normal left atrial voltage. Methods: Consecutive patient registry analysis was performed on all patients with pAF and normal left atrial voltage undergoing initial radiofrequency ablation from November 1, 2018 to November 15, 2019. Primary endpoint was recurrence of atrial arrhythmia including AF, atrial tachycardia (AT), or atrial flutter (AFL). Results: A total of 321 patients were studied, 214 in the PVI group and 107 in the PWI + PVI group. Recurrence of any atrial arrhythmia occurred in 18.2% of patients in the PVI group and 16.8% in the PVI + PWI cohort ( p = 0.58). At 1 year, recurrence was 14.0% in the PVI group and 15.0% in the PWI + PVI group ( p = 0.96). There was a lower AT/AFL recurrence in the PVI + PWI group, not reaching significance (3.7% in the PWI + PVI group vs. 7.9% in PVI group, p = 0.31). Need for carina lesions predicted recurrence in the PVI‐only group. Conclusions: Addition of PWI to PVI in pAF patients undergoing their first ablation did not reduce the frequency of atrial arrhythmia recurrence. This warrants further study in a prospective trial.